Economic Growth After Debt Surges - Jalles, Joao Tovar (IMF Working Papers; Working Paper ;, 2022)
Debt levels, both private and public, were already at record highs before the Covid-19 pandemic, and surged further in 2020. The high indebteness raises concerns whether it will undermine future growth prospects. This paper contributes to the ongoing debate by examining what happens to economic growth after debt surges. We apply a local projection method to a new dataset of debt surges in 190 countries between 1970 and 2020. Our results show that the relationship between debt surges and economic growth are complex. Debt surges tend to be followed by weaker economic growth and persistently lower output. However, this negative relationship does not always hold. Surges in public debt tend to have the most negative impact on future growth prospects. This is particularly the case if the economy is already operating with a large positive output gap. Debt surges also tend to be followed by weaker economic growth if the initial debt levels are high, especially for private debt surges. Our results also show how debt surges impact future growth. Public debt surges are associated with especially weaker private and public investment, although both private and public consumption are also negatively affected. Surges in corporate debt are followed by lower private and public investment.